Medication Adherence Among Elderly With Hypertension: Johnson Model-based Program - Fatemeh Melali; Habibollah Hoseini; Mahin Moeini (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives Hypertension is the most common cause of stroke and kidney failure in the elderly and medication adherence is vital in controlling complications. This study aims to determine the effect of the Johnson model-based program on medication adherence among the elderly with hypertension. Methods & Materials The present study was a clinical trial that was performed on the elderly with hypertension referred to the Shahid Aval comprehensive health service center in Isfahan City, Iran. Through the convenience sampling method, 70 older adults were selected and randomly divided into intervention and control groups. For the intervention group, 6 sessions of a family-based medication adherence program were performed based on the Johnson model. Demographic characteristics questionnaire and sphygmomanometer were used to collect data. Data were analyzed by SPSS version 22 statistical software using independent t test, Chi-square, and repeated measures analysis of variance (ANOVA). Results No difference was observed between the two groups in terms of the distribution of demographic characteristics. Mean systolic and diastolic blood pressure before the intervention in the group were not significantly different, but immediately and three months after the intervention in the intervention group, it was significantly lower than the control group(P<0.05). Conclusion Johnson's model-based program was effective in lowering hypertension in the elderly. Therefore, the method used in the present study is proposed to older adults and elderly care nurses as a simple, non-invasive, low-cost, and effective method of reducing hypertension.